(untitled) (Quinto Sol, 2022)
During the second half of the 20th century, Catamarca tried two constitutional reforms that expressed tendencies of each context, the first in 1965 and the second in 1988, and that were representative of its social framework. For this reason, we will place ourselves in the analysis of the reform projects and the texts sanctioned as provincial supreme law, taking into account the guidelines of said experiences: the liberal (secular) tendency and the clerical tendency. Catamarca can be characterized as a space of a traditional nature, where the weight of the Catholic Church represents an inescapable factor in power relations, since its presence was decisive, a key actor at a time when the legal and political order of the provincial society was defined; to such an extent that it has a very solid power of challenge. This was demonstrated in the last constitutional reform, in 1988, when it managed to capture some of its principles in the Magna Carta and tried to make the provincial State a quasi-religious organization. In the reform of 1965, the position of the constituents had been different, since principles closer to a secular State prevailed, which generated angry criticism from the Church. In this article we will observe this dichotomy between laity and clergy, going through the relationship between political parties and the Catholic Church, which will allow us to reconstruct a scenario crossed by a broader debate regarding the modernization of the province that impregnated the constitutional norm; in addition to undressing joints of political crises that were a constant in the three decades after the first Peronism.